Fuel Cell Evolution (The International Journal for Scientific Research, 2023)
This paper focuses on the progress that has been made in fuel cells through four theories, namely thermodynamics, electrochemistry, electrolyte theories, direct generation physics and finally the application of Ohm's law physics to the fuel cell system. In order to identify the compatibility of the basic theories with these systems. Through this research, we have indicated the need for a unified theory to explain the mechanism of stability and constancy, which leads us to say that they are relatively perfect systems.
Keywords: fuel cell; electrochemical reaction; electrode; electrolyte; power generation; AFC; PAFC; PEFC; MCFC; SOFC; Exchange current density; charge transfer coefficient; ohm losses; resistance